2019
DOI: 10.25077/jip.3.1.32-47.2019
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Abstrak. Engagement pada aktivitas belajar adalah hal yang penting guna mendapatkan ilmu pengetahuan dan keterampilan yang diberikan di sekolah. Penelitian-penelitian terdahulu mengenai engagement membuktikan bahwa engagement adalah prediktor dari proses belajar siswa, hasil belajar, retensi dan kelulusan siswa. Oleh karena itu, untuk bisa membuat siswa lebih engage dengan aktivitas belajar, perlu diketahui faktor-faktor yang dapat memengaruhi engagement tersebut. Pada penelitian ini akan dikaji mengenai penga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…As a follow-up, it is necessary to carry out further research on the influence of positive emotions in online learning on student engagement. Previous studies also found that engagement is also influenced by meeting the needs of the students themselves [24], [25]. Therefore, it is interesting to explore the relationship between emotions and the fulfillment of students' basic psychological needs.…”
Section: Figure 1 Spider Plot Of Student's Achievement Emotionmentioning
confidence: 98%
“…As a follow-up, it is necessary to carry out further research on the influence of positive emotions in online learning on student engagement. Previous studies also found that engagement is also influenced by meeting the needs of the students themselves [24], [25]. Therefore, it is interesting to explore the relationship between emotions and the fulfillment of students' basic psychological needs.…”
Section: Figure 1 Spider Plot Of Student's Achievement Emotionmentioning
confidence: 98%